Analysis of combined pressure-driven and electroosmotic hydrothermal features of non-Newtonian nanofluid in variable cross-section microchannel with slip-dependent zeta potential - Debanjan Banerjee; Sukumar Pati; Pankaj Biswas; László Baranyi (Alexandria Engineering Journal)
The present study investigates the hydrodynamic and thermal behavior of combined electroosmotic and pressure-driven flow of non-Newtonian nanofluid through a variable cross-section microchannel considering the effects of slip-dependent zeta potential, magnetic field, Joule heating, viscous dissipation and thermal radiation. The closed-form expressions of electrical double-layer potential, velocity, and temperature distributions have been derived using a biviscosity model of non-Newtonian fluid to compute the shear stress and Nusselt number (Nu). The divergence in the microchannel strengthens the influence of the magnetic field and weakens the influence of hydrodynamic slippage on the axial velocity. Moreover, the variation in channel height significantly affects the shear stress, with substantial impacts of the Hartmann number and apparent viscosity. The Nusselt number (Nu) increases with the divergence in the geometry and such increasing rate is higher for lower Hartmann numbers. Nusselt number becomes zero for higher radiation parameters in the narrow portion of the microchannel and alters significantly due to the apparent zeta potential. The nanoparticle volume fraction has a marginal effect on Nu except at the position of maximum channel height.